Environmental Offences in the Legal System of Republic Serbia - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The author of this paper elaborates on the problems of environmental offences, starting from the effort to formulate logic and the system of environmental offences at the level of the national legislature. In the second place, the results of the author’s research point to the prerequisites and apparatus necessary for the perpetrator of environmental offences. Text also indicates some observed contradictions in the environmental offences forming at the level of the Republic of Serbia legislature. Finally, the author points out which logical rules and methods have to be respected and employed in the efforts of future environmental law reconstructions, especially in the part oriented on environmental offences.